2011
DOI: 10.1016/j.jaci.2010.12.1111
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of peanut oral immunotherapy: Clinical desensitization and modulation of the allergic response

Abstract: Background-Open-label oral immunotherapy (OIT) protocols have been used to treat small numbers of patients with peanut allergy. Peanut OIT has not been evaluated in double-blind, placebo-controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
477
5
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(514 citation statements)
references
References 25 publications
27
477
5
5
Order By: Relevance
“…3), which likely corresponds to the reduction of the numbers of IgEproducing cells. This result was concordant with the results based on serum peanut-specific IgE levels (P = 0.034 and 0.62, respectively, in OIT and placebo groups), and also several reports demonstrating that serum peanut-specific IgE levels were significantly decreased by the treatment of OIT [13,21,24,25]. We observed one common IGHE clone among two pre-treated OIT and five pre-treated placebo samples (Supplementary Table 5), but this clone was still retained in the samples after OIT and placebo treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3), which likely corresponds to the reduction of the numbers of IgEproducing cells. This result was concordant with the results based on serum peanut-specific IgE levels (P = 0.034 and 0.62, respectively, in OIT and placebo groups), and also several reports demonstrating that serum peanut-specific IgE levels were significantly decreased by the treatment of OIT [13,21,24,25]. We observed one common IGHE clone among two pre-treated OIT and five pre-treated placebo samples (Supplementary Table 5), but this clone was still retained in the samples after OIT and placebo treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we analyzed the samples obtained in a randomized controlled study of peanut OIT reported previously [13]. Among them, we studied 12 subjects who received peanut OIT and 5 subjects received a placebo due to the sample limitation.…”
Section: Patient Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the OIT protocols to date have demonstrated an increase in Th1 type cytokines. Furthermore, the only description of low levels of Th2 type cytokines (IL-5 and IL-13) produced from PBMCs was reported in two OIT protocols for peanut allergy (Blumchen et al 2010;Varshney et al 2011). Figure 3 summarizes the immunological mechanisms of OIT for food allergies that have been described to date.…”
Section: Mechanisms Of Oit In Food Allergymentioning
confidence: 99%
“…Most recently, 1 controlled study was performed in the United States and another uncontrolled one in Europe. [61][62] the details of all uncontrolled and controlled studies are summarized in Table 1. [56-58-59-61-62].…”
Section: Studies Of Oit For Peanut and Tree Nut Allergiesmentioning
confidence: 99%